2012
DOI: 10.1002/hyp.9286
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir storage for managing floods in urban areas: a case study of Dzorwulu basin in Accra

Abstract: The study simulated the effect of using reservoir storage for reducing flood peaks and volumes in urban areas with the Dzorwulu basin in Accra, Ghana as case study. A triangulated irregular network surface of the floodplain was created using ArcGIS from ESRI by integrating digital elevation model and the map of the study area. The weighted curve number for the basin was obtained from the land use and soil type shape files using ArcGIS. The Soil Conservation Service curve number unit hydrograph procedure was us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Models dealing with the prediction or reconstruction of flood hydrographs are common, among them palaeo-flood hydrology and rainfall-run-off process simulation and flood routing (El-Hames and Richards, 1998;Sharma and Murthy, 1998;Greenbaum et al, 2001;Morin et al, 2001Morin et al, , 2009Costelloe et al, 2003;Milewski et al, 2009;Capart, 2013;Owusu et al, 2013;Greenbaum et al, 2014). With palaeo-flood hydrology, the main issue is reconstruction of the envelope curve for peak discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Models dealing with the prediction or reconstruction of flood hydrographs are common, among them palaeo-flood hydrology and rainfall-run-off process simulation and flood routing (El-Hames and Richards, 1998;Sharma and Murthy, 1998;Greenbaum et al, 2001;Morin et al, 2001Morin et al, , 2009Costelloe et al, 2003;Milewski et al, 2009;Capart, 2013;Owusu et al, 2013;Greenbaum et al, 2014). With palaeo-flood hydrology, the main issue is reconstruction of the envelope curve for peak discharge.…”
Section: Introductionmentioning
confidence: 99%
“…With palaeo-flood hydrology, the main issue is reconstruction of the envelope curve for peak discharge. This information can serve as input for an assessment of flow volume (Jacoby et al, 2008), transmission losses (Greenbaum et al, 2001) or hazards (El Bastawesy et al, 2009;Owusu et al, 2013). In the field of rainfall-run-off modelling, the focus is often on flood hydrograph prediction.…”
Section: Introductionmentioning
confidence: 99%
“…Models dealing with the prediction or reconstruction of flood hydrographs are common, among them rainfall-runoff process simulation and flood routing [7][8][9][10][11][12][13][14][15][16][17]. In the field of rainfall-runoff modelling, the focus is often on flood hydrograph prediction.…”
mentioning
confidence: 99%
“…HEC-RAS was used to model reservoir storage, assess different types of river morphological data, assess a potential dam breach, develop a new method for real-time flood management in riverreservoir systems, demonstrate a 1-D jokulhlaup simulation, determine flood frequency, quantify hydrogeomorphic processes that influence alluvial gully erosion along a fluvial megafan, and compute water levels in a channel network (Owusu et al 2013, Saleh et al 2013, Yochum et al 2008, Malekmohammadi et al 2010, Alho and Aaltonen 2008, Maingi and Marsh 2002, Shellberg et al 2013, Knebl et al 2005 . From the case studies, it is shown that when channel cross-sectional data is unavailable, cross-sections can be created from high resolution DEMs (Knebl et al 2005, Yochum et al 2008, Owusu et al 2013, Shellberg et al 2013. Owusu et al (2013) completed a case study in the Dzorwulu basin in Accra, Ghana simulating the incorporation of reservoir storage to analyze the effects on the reduction of flood peaks and volume in urban areas.…”
Section: Hec-ras Case Studiesmentioning
confidence: 99%
“…From the case studies, it is shown that when channel cross-sectional data is unavailable, cross-sections can be created from high resolution DEMs (Knebl et al 2005, Yochum et al 2008, Owusu et al 2013, Shellberg et al 2013. Owusu et al (2013) completed a case study in the Dzorwulu basin in Accra, Ghana simulating the incorporation of reservoir storage to analyze the effects on the reduction of flood peaks and volume in urban areas. Longitudinal and cross-sectional channel characteristics were determined from a field survey, and combined with a TIN model to establish surface elevations.…”
Section: Hec-ras Case Studiesmentioning
confidence: 99%